SAÚDE E AMBIENTE DE TRABALHO DO SERVIDOR PÚBLICO FEDERAL DO MARANHÃO: visão da perícia médica - SERRA NETO, Artur (2017)
Introduction: Attention Integrated Subsystem Health of the Federal Civil Servants (SIASS) was created to support the Care Policy Health Care Server. Has aimed to coordinate and integrate actions and programs in the health care areas, official expertise, promotion, prevention and health monitoring of servers of the federal administration. From the perception as an expert medical SIASS-UFMA Unit, the following question arose: What are the conditions that generate more departures on the servers? Is there a relationship with your desktop? Objective: To describe the epidemiological profile of the main pathologies that affect civil servants attended at the medical expertise of industry and correlate them with their work environment. Methodology: From reports obtained from the electronic medical record, SIAPE HEALTH, in the years 2011, 2012 and 2013 was made a descriptive analysis and later, to make the association of categorical variables with the years collection was performed nonparametric chi -square of independence (χ2). Results: The sick servants are mostly women, in the age group of 31 to 40 years (p <0.0001), who work in the University Hospital exercising the function of nursing professionals and suffering from musculoskeletal disorders and mental disorders. Doctors, the secondlargest in the hospital, are away for a few days from musculoskeletal and gastrointestinal diseases. Road policemen working in an often dangerous environment are also affected by mental and musculoskeletal disorders. It was evident that the work environment of the University Hospital needs a more detailed analysis and a better interaction with the three axes of this policy. Conclusion: It is not only the physical environment that brings problems, but all the psycho-emotional involvement of their working relationships. Not being able to consider these diseases as occupational, but in many of them there is a relation with the work environment. It is concluded that this information can help the managers of the institution in the formulation of preventive measures so as to avoid further sick leave and promote a healthier environment.